Analisis Kinerja Operasi Perusahaan yang Melakukan Merjer atau Akuisisi - Yudhanti, Ceicilia Bintang Hari (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2005)
The aim of this study is to analyze operating performance of merger or acquisition firms. Commonly, the motivation of company to commit merger or acquisition is to reach synergy. Moreover, this synergy in particular way can be analyzed by company's operating performance. This study uses financial ratios to measure company performance.